PEMBUATAN KARYA LUKIS MELALUI PEMANFAATAN LIMBAH BOTOL BEKAS - Rumekso, Kunto Adi (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2024)
The creation of artworks cannot be hindered by anything, but what becomes an obstacle in creating works is the presence or absence of inspiration which can then foster creativity. The existence of inspiration will certainly be found by someone if they have the intention to create a work, otherwise if it is forced, there will be no inspiration that builds creativity. The ability to read opportunities and find a way through also greatly impacts the success of creating works that have value in them Ease of access to information or problem solving becomes very useful if used in exploring ideas or insights instead of being used for things that are not useful in the long run. The purpose of this workshop activity is to equip students as the audience to be able to seize opportunities by utilizing glass bottle waste as the main material in creating works of art or to be used as goods of selling value.